Pandangan John Finnis Mengenai Hukum Yang Tidak Adil - Bello, Petrus CKL (UI Scholars Hub, 2023)
Contemporary natural law thinker John Finnis in his book Natural Law and Natural Right published in 1980 differentiates between legal obligations and moral obligations. According to Finnis, legal obligations cannot change, while moral obligations can change, in the sense that when it comes to unjust laws, only the moral obligation to obey the unjust law is extinguished, while the legal obligation to obey the unjust law remains and is binding. For Finnis, natural law theory does not focus on the view that the law is wrong or against moral principles that cannot be called law (lex injusta non est lex), but focuses on the common good, and formulates how the legal system can strive for it. Although we do not have a moral obligation to obey unjust laws, in certain situations we still have a moral obligation to obey unjust laws to keep the legal system as a whole stable. The distinction or separation of legal obligations and moral obligations made by Finnis is weak in its relevance to unjust laws, as pointed out by his critics, namely Robert Alexy and Seow Hon Tan.